The use of Latinx in public health research when referencing Hispanic or Latino populations. (June 2022) - Borrell, Luisa N.; Echeverria, Sandra E.
Abstract: We provide a brief description of the demographics of the Hispanic or Latino population in the United States; point out the origin of the term Hispanic or Latino as standardized terminology in general including public health research; discuss the use of Latinx among the Hispanic or Latino population; and suggest recommendations for the use of Latinx in research including Hispanic or Latino populations. The Hispanic or Latino population is a heterogenous population familiar with name and/or labeling controversies since the introduction of the ethnicity category in the 1980 U.S. Census. Latinx, a term aiming to be gender-expansive, inclusive, and/or neutral, is being used to refer to the Hispanic or Latino population overall. However, only a small proportion of this population has heard or use the term. For research purposes, we recommend that 1) the population is referred to using the labels used during data collection for existing data; 2) when using Latinx, participants are explained the meaning of the term and other choices be provided; and 3) investigations using Latinx should interpret the results within the current context of the term and acknowledge the group (s) to which the findings apply. The latter will lead to accurately represent the Hispanic or Latino population. This correct identification is important to document and address health inequities across race and ethnicity in the U.S. Highlights: Latinx was added to the Merrian-Webster dictionary in 2018. The term Latinx aims to represent gender diversity. A small proportion of the Hispanic or Latino population uses the term (2%–4%). Latinx when conflated with ethnic identity is not achieving its inclusivity's goal. Researchers should use and define Latinx as identifier during data collection.